Collaboration and Teamwork in the Health Professions: Rethinking the Role of Conflict. (April 2018) - Eichbaum, Quentin
Abstract : Whereas the business professions have long recognized that conflict can be a source of learning and innovation, the health professions still tend to view conflict negatively as being disruptive, inefficient, and unprofessional. As a consequence, the health professions tend to avoid conflict or resolve it quickly. This neglect to appreciate conflict's positive attributes appears to be driven in part by (1) individuals' fears about being negatively perceived and the potential negative consequences in an organization of being implicated in conflict, (2) constrained views and approaches to professionalism and to evaluation and assessment, and (3) lingering autocracies and hierarchies of power that view conflict as a disruptive threat. The author describes changing perspectives on collaboration and teamwork in the health professions, discusses how the health professions have neglected to appreciate the positive attributes of conflict, and presents three alternative approaches to more effectively integrating conflict into collaboration and teamwork in the health professions. These three approaches are (1) cultivating psychological safety on teams to make space for safe interpersonal risk taking, (2) viewing conflict as a source of expansive learning and innovation (via models such as activity theory), and (3) democratizing hierarchies of power through health humanities education ideally by advancing the health humanities to the core of the curriculum. The author suggests that understanding conflict's inevitability and its innovative potential, and integrating it into collaboration and teamwork, may have a reassuring and emancipating impact on individuals and teams. This may ultimately improve performance in health care organizations.